THE INFLUENCE OF FEAR OF MISSING OUT AND BRAND REPUTATION ON PURCHASE INTENTION OF APPLE PRODUCTS - Towoliu, Rivaldy; Tumbuan, Willem J. F. A.; Pandowo, Merinda H. C. (Universitas Sam Ratulangi, 2024)
Technological development is an ongoing and inevitable phenomenon in the modern world. Devices, such as smartphones, tablets, laptops have become a very important medium in facilitating the development of this technology. They enable quick access to information, entertainment, as well as applications that make everyday tasks easier. This study aims to analyze the Influence of Fear of Missing Out and Brand Reputation on Purchase Intention of Apple Products. This research is approached by an associative quantitative method. Data collection was carried out through a questionnaire distributed to 100 respondent of Gen-Z (17-27 years old). The data is analyzed using multiple linear regression model with SPSS 27 software. The findings obtain shows that there is a significant influence of Fear of Missing Out on Purchase Intention. Then, brand reputation also significantly influences purchase intention. Lastly, Fear of missing out and brand reputation simultaneously influence purchase intention. These findings indicate that people especially Gen-Z, who experienced FOMO will formulate a desire to purchase a product. Also, a reputation of a brand plays a crucial role in the consideration process before purchasing the product. The better the reputation the more intention for people to buy the product. Kata Kunci: Purchase Intention, Fear of Missing Out (FOMO), Brand Reputation